Analisis Psikometri Morbid Curiosity Scale Versi Bahasa Indonesia - Adriansyah, Galih; Putri, Arinta Aisyah; Qalbyna, Galih Khalisha; Febriani, Safira; Wyandini, Diah Zaleha; Hidayat, Ghinaya Ummul Mukminin (Journal of Research and Measurement in Psychology: JPPP, 2025)
Indonesians have a high interest in the mystical, horror and crime, which is reflected in the popularity of themed content that can lead to risky activities such as urban exploration. This phenomenon is related to morbid curiosity, a curiosity about horrific things such as death and violence, which can influence dangerous explorative behavior. In order to measure this interest and prevent risky behavior, researchers adapted the Morbid Curiosity Scale into an Indonesian version. During the analysis, this measuring instrument was given to 258 participants with male or female criteria, minimum age of 18 years and had a special interest in horror, thriller, supernatural, and crime themes. Based on item analysis using item-rest correlation and Confirmatory Factor Analysis, the reliability of the Indonesian version of the Morbid Curiosity Scale measuring instrument totaling 24 items shows a Cronbach's alpha value of 0.894 and chi-square test p-value of less than 0.001, CFI of 0.840, GFI of 0.954, and RMSEA of 0.079 which means that this scale cannot yet be used because the model does not fit even though the reliability is good. This study has limitations in terms of cultural differences that affect the understanding of items, especially items with a Western cultural context, so further research is needed so that the instrument can be used in the Indonesian cultural context. This instrument is expected to be useful for understanding how curiosity about frightening, mystical, and dangerous phenomena, both in digital media and in everyday life, plays a role in individual behavior.